Perceived Environmental Pollution and Its Impact on Health in China, Japan, and South Korea - Kamimura, Akiko (J Prev Med Public Health, 2017)
OBJECTIVES: Environmental pollution is a significant global issue. Both objective (scientifically measured) environmental pollution and perceived levels of pollution are important predictors of self-reported health. The purpose of this study was to compare the associations between perceived environmental pollution and health in China, Japan, and South Korea. METHODS: Data were obtained from the East Asian Social Survey and the Cross-National Survey Data Sets: Health and Society in East Asia, 2010 (n=7938; China, n=3866; Japan, n=2496; South Korea, n=1576). RESULTS: South Koreans perceived environmental pollution to be the most severe, while Japanese participants perceived environmental pollution to be the least severe. Although the Japanese did not perceive environmental pollution to be very severe, their self-rated physical health was significantly related to perceived environmental pollution, while the analogous relationships were not significant for the Chinese or Korean participants. Better mental health was related to lower levels of perceived air pollution in China, as well as lower levels of perceived all types of pollution in Japan and lower levels of perceived noise pollution in South Korea. CONCLUSIONS: Physical and mental health and individual socio-demographic characteristics were associated with levels of perceived environmental pollution, but with different patterns among these three countries.